Deconstructing an infamous extinction crisis: Survival of Partula species on Moorea and Tahiti - Amanda E. Haponski; Taehwan Lee; Diarmaid Ó Foighil (Evolutionary Applications, 2019)
Abstract Eleven of eighteen Society Island Partula species endemic to the Windward Island subgroup (Moorea and Tahiti) have been extirpated by an ill‐advised biological control program. The conservation status of this critically endangered tree snail radiation is of considerable import, but is clouded by taxonomic uncertainty due to the extensive lack of congruence among species designations, diagnostic morphologies, and molecular markers. Using a combination of museum, captive, and remnant wild snails, we obtained the first high‐resolution nuclear genomic perspective of the evolutionary relationships and survival of fourteen Windward Island Partula species, totaling 93 specimens. We analyzed ~1,607–28,194 nuclear genomic loci collected with the double digest restriction‐site associated sequencing method. Results from phylogenomic trees, species estimation, and population assignment tests yielded monophyly of the Windward Island subgroup. Within this group, two well‐supported clades encompassing five species complexes were recovered. Clade 1 was restricted to Tahiti and contained two species complexes: “P. affinis” (three species) and “P. otaheitana” (five species). Clade 2 occurred on Moorea and on Tahiti and consisted of three species complexes: one Tahitian, “P. clara/P. hyalina”; the other two, “P. taeniata” (three species) and “P. suturalis” (six species), Moorean. Our genomic results largely corroborated previous mitochondrial DNA survival estimates for Moorea and Tahiti, with all five species complexes having members surviving in captivity and/or as remnant wild populations, although the details vary in each case. Continued, proactive conservation and management may yet ensure a phylogenetically representative survival of the fabled Partula species of Moorea and Tahiti.